The underground of European cities in planning documents: the case of A Coruña (Spain). (2017) - Lois González, Rubén C.; Ulloa, Beatriz Moar; Otón, Miguel Pazos
Abstract: The knowledge of the underground is a key issue for cities in the beginning of the 21st century. So far, only very few european cities have included the underground in their planning documents and management. There is an evident gap between north and south of Europe, as it was clear in the COST SUBURBAN action, carried out by a consortium of 29 different european countries. In this action, several case studies from different parts of Europe were examined, including the sucessful cases of Rotterdam, Glasgow, Oslo, Hamburg, Odense and others, all of them in Northern Europe. Spain was represented by the case of A Coruña, a coastal city in the northwest of the Iberian Peninsula. This text focus on the analysis of the level of development between urban planning and the knowledge of the underground. In particular, attention is paid to the treatment of the underground in the current planning and its importance in urbanism and local planning.